Corrigendum to “Experimental investigations of number of blades effect on archimedes spiral wind turbine performance” [MESI Vol. 4, No. 2 (2024) pp 198-209]: Refers to: https://doi.org/10.31603/mesi.12373 - Agus Dwi Korawan; Rosadila Febritasari (Universitas Muhammadiyah Magelang, 2025)
In the original article (https://doi.org/10.31603/mesi.12373), there was a mistake in Paragraph 3 (1. Introduction), Paragraph 1 (2.2.1. The archimedes spiral wind turbine (ASWT) design), Table 1 (2.2.2.Mesh generation), Paragraph 1, 2 and 3 (3.1. Experimental result) and 4. Conclusion as published. The mistake involves the use of a comma (,) instead of a period (.) and vice versa in writing numerical values, as well as missing citations. The editor and author have communicated and agreed to correct this issue to avoid misleading readers.All corrections are provided in detail in the PDF file.